The Impact of r-g on the Euro-Area Government Spending Multiplier - di Serio, Mario (IMF Working Papers; Working Paper ;, 2021)
We compute government spending multipliers for the Euro Area (EA) contingent on the interestgrowth differential, the so-called r-g. Whether the fiscal shock occurs when r-g is positive or negative matters for the size of the multiplier. Median estimates vary conditional on the specification, but the difference between multipliers in the negative and positive r-g regimes differs systematically from zero with very high probability. Over the medium run (5 years), median cumulated multipliers range between 1.22 and 1.77 when r-g is negative, and between 0.51 and 1.26 when r-g is positive. We show that the results are not driven by the state of the business cycle, the monetary policy stance, or the level of government debt, and that the multiplier is inversely correlated with r-g. The calculations are based on the estimates of a factor-augmented interacted panel vector-autoregressive model. The econometric approach deals with several technical problems highlighted in the empirical macroeconomic literature, including the issues of fiscal foresight and limited information.